2021
DOI: 10.1108/ijtc-08-2020-0168
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of crisis reactions toward major disease outbreaks: application of the triple helix model in the context of tourism

Abstract: Purpose While academia, industry and government have made various efforts to ameliorate the impacts of Covid-19, no study has hitherto used an integrative framework to assess the reactions of all three of these sectors to previous multinational epidemics. Such fragmentation ignores the holistic nature of crisis management. To better understand the impacts of health crises on tourism, this study aims to examine the past literature related to academic, industrial and governmental responses to multinational epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 53 publications
0
16
0
2
Order By: Relevance
“…Berbekova et al, 2021;Li et al, 2022;Wut et al, 2021). Chen et al (2022) identify that, although previous epidemic research has highlighted consumers' perceptions of risk and associated changes to their travel behavior, potential strategies for ameliorating such behavioral changes while maintaining safety and security have largely been ignored (Ding et al, 2022;Ho et al, 2022;Simonetti and Bigne, 2022). This paper addresses this concern by offering an empirical study in which (1) it is shown that the use of health and safety protocols contributes to the generation of a higher perceived value and intention to visit the hotel (compared to hotels that do not use a health and safety protocol) and ( 2) evaluated the moderating role of the hotel brand awareness on the effects that the use of health and safety protocols on perceived value and the intention to stay at the hotel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berbekova et al, 2021;Li et al, 2022;Wut et al, 2021). Chen et al (2022) identify that, although previous epidemic research has highlighted consumers' perceptions of risk and associated changes to their travel behavior, potential strategies for ameliorating such behavioral changes while maintaining safety and security have largely been ignored (Ding et al, 2022;Ho et al, 2022;Simonetti and Bigne, 2022). This paper addresses this concern by offering an empirical study in which (1) it is shown that the use of health and safety protocols contributes to the generation of a higher perceived value and intention to visit the hotel (compared to hotels that do not use a health and safety protocol) and ( 2) evaluated the moderating role of the hotel brand awareness on the effects that the use of health and safety protocols on perceived value and the intention to stay at the hotel.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the development of greater knowledge is required about the effects of strategies implemented at hotel level -such as the use of health and safety protocols which could influence the intention to visit the hotels (Wut et al, 2021). In accordance with the knowledge gaps set out by Chen et al (2022) and Li et al (2022), and based on the potential for influence, research for this paper is aimed at advancing knowledge about whether the use of health and safety protocols by hotels contributes to achieving a greater intention to visit, compared to that achieved by hotels not using health and safety protocols. This leads to the second research question.…”
Section: Intention To Visit: the Effect Of The Use Of Health And Safe...mentioning
confidence: 99%
“…Berbekova et al, 2021;Li et al, 2022;Wut et al, 2021). Chen et al (2022) found that although previous epidemic research has foregrounded consumers' perceptions of risk and associated changes to their travel behaviour, potential strategies for ameliorating such behavioural changes while maintaining safety and security have mainly been ignored. Such strategies should not simply be applied, but preferably carefully measured by researchers for their impacts on consumers' behaviour.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…, 2021). Chen et al. (2022) found that although previous epidemic research has foregrounded consumers’ perceptions of risk and associated changes to their travel behaviour, potential strategies for ameliorating such behavioural changes while maintaining safety and security have mainly been ignored.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…Elkhwesky, Salem, et al (2022) noted in their systematic literature review that there exists a scarcity of research on the antecedents, outcomes, and integrating theories about sustainable hospitality practices. Some noteworthy studies include ‘assessment of tourism environmental impacts for the post‐COVID era (Candia & Pirlone, 2021)’, ‘impact of tourism on the environment amid COVID‐19 (Nagaj & Žuromskaitė, 2021)’, ‘COVID‐19 crisis vis‐à‐vis sustainability in the hospitality sector (Jones & Comfort, 2020)’, ‘waste management in hospitality for the post‐Covid scenario (Filimonau, 2021)’, ‘impacts of COVID‐19 on ecotourism (Soliku et al, 2021)’, ‘COVID‐19 and African tourism research agenda (Rogerson & Baum, 2020)’, ‘emerging issues and challenges in Indian tourism and hospitality business (Sanjeev & Tiwari, 2021), “tourism in South Africa during COVID‐19 (Musavengane & Leonard, 2022)” Specific exemplary systematic literature reviews and bibliometric analysis‐based studies include ‘sustainability perspectives in tourism and hospitality industry (Lima Santos et al, 2020)’, ‘advancing environmental knowledge in the hospitality industry in Covid society (Martínez‐Martínez et al, 2022)’, ‘resilience of tourism and hospitality industry amid COVID‐19 (Altshuler & Schmidt, 2021)’, ‘comparison of health‐related crisis in tourism and hospitality context (Park et al, 2022)’, ‘crisis reactions towards major disease outbreaks in the tourism context (Chen et al, 2021)’, ‘COVID‐19 and tourism (Utkarsh & Sigala, 2021)’, ‘trends of COVID‐19 and tourism (Viana‐Lora & Nel‐Lo‐Andreu, 2022)’, ‘themes for tourism and hospitality education post‐COVID‐19 (Menon et al, 2021)’, ‘utilizing technology tools to tackle COVID‐19 challenges in travel and tourism (Ndou et al, 2022)’, and ‘hospitality and tourism under COVID‐19 (Wang et al, 2022)’.…”
Section: Introductionmentioning
confidence: 99%